2014
DOI: 10.1208/s12248-014-9697-1
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of MHC-I Antigen Presentation via Architectural Control of pH-Responsive, Endosomolytic Polymer Nanoparticles

Abstract: Protein-based vaccines offer a number of important advantages over organism-based vaccines but generally elicit poor CD8(+) T cell responses. We have previously demonstrated that pH-responsive, endosomolytic polymers can enhance protein antigen delivery to major histocompatibility complex class I (MHC-I) antigen presentation pathways thereby augmenting CD8(+) T cell responses following immunization. Here, we describe a new family of nanocarriers for protein antigen delivery assembled using architecturally dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
60
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 55 publications
(79 reference statements)
1
60
0
Order By: Relevance
“…The two cores (and a linear copolymer) were then used as macro-RAFT agents to control copolymerization of dimethyl acrylamide (DMA) and pyridyl disulfide methacrylamide (PDSMA) to produce star-nanogels (Scheme 22). This work (189) demonstrated that the architecture of pH-responsive, endosomolytic polymers can have a dramatic effect on intracellular antigen delivery, and indicated a promising strategy for enhancing CD8 + T cell responses to protein-based vaccines.…”
Section: Star Polymer Synthesis (Core-crosslinked Stars Star-nanogels)mentioning
confidence: 88%
See 2 more Smart Citations
“…The two cores (and a linear copolymer) were then used as macro-RAFT agents to control copolymerization of dimethyl acrylamide (DMA) and pyridyl disulfide methacrylamide (PDSMA) to produce star-nanogels (Scheme 22). This work (189) demonstrated that the architecture of pH-responsive, endosomolytic polymers can have a dramatic effect on intracellular antigen delivery, and indicated a promising strategy for enhancing CD8 + T cell responses to protein-based vaccines.…”
Section: Star Polymer Synthesis (Core-crosslinked Stars Star-nanogels)mentioning
confidence: 88%
“…In a recent study on the preparation of a new family of nanocarriers for protein antigen delivery (189), two variants were exploited. In the first, a hyperbranched core was formed by copolymerization of BMA and 2-(N,N-diethylamino)ethyl methacrylate) (DEAEMA) was mediated by an "inimer" RAFT agent.…”
Section: Star Polymer Synthesis (Core-crosslinked Stars Star-nanogels)mentioning
confidence: 99%
See 1 more Smart Citation
“…These include peptide amphiphile micelles [9], pH responsive polymer-based nanoparticles [10], cationic liposomes [11], polysaccharide-based nanoparticles [12], and nanoparticles formed from biodegradable polymers such as p o l y l a c t i c -c o -g l y c o l i d e ( P L G A ) [ 1 3 -1 5 ] and polyanhydrides [16]. This theme issue includes a comprehensive review by Jewell and colleagues on the topic of harnessing biomaterials to engineer the lymph node microenvironment for immunity or tolerance [17].…”
mentioning
confidence: 99%
“…Upon vaccination of mice with these micelles, a potent IgG1 antibody response was induced that was similar to responses obtained from co-administration of soluble peptide with two classical adjuvants. Stayton and colleagues report on the enhancement of MHC-I antigen presentation via architectural control of pH-responsive endosomolytic polymer nanoparticles [10]. In their study, increased MHC-I antigen presentation was observed in vitro with antigenloaded nanoparticles formulated from hyperbranched and cross-linked polymer structures compared to soluble antigen or antigen-loaded nanoparticles made from linear polymers.…”
mentioning
confidence: 99%